Peranan Otoritas Jasa Keuangan (OJK) Sebagai Lembaga Muhtasib Dalam Industri Keuangan Syariah di Indonesia - Abdul Salam; Syaiful Muhammad Irsyad (JESI (Jurnal Ekonomi Syariah Indonesia), 2019)
In Indonesia, one of the institutions that can be considered a Muhtasib institution in the sharia financial sector is the Financial Services Authority (OJK). As Law Number 21 of 2011, the OJK has the function of organizing an integrated system of regulation and supervision of all activities in the financial services sector which include financial service activities in the Banking sector; financial service activities in the Capital Market sector; and financial service activities in the Insurance, Pension Funds, Financing Institutions and Other Financial Services Institutions sectors, including the Islamic finance industry sector. This study will unravel the extent of the role of the FSA as the Muhtasib in the Islamic finance industry in Indonesia, especially in the regional areas of Central Java and D.I. Yogyakarta.This research did 2 (two) kinds of research, they are field of study and literature study. The collecting data of this research through observation and non-structured interview. The methode of data collection is conducting  interviews  with  the Central Java OJK, OJK D.I. Yogyakarta.The conclusion of this study is that the role of the Financial Services Authority (OJK) in Regional Region 3 of Central Java and Yogyakarta as a Muhtasib institution in supervising the Islamic financial industry in Central Java and Yogyakarta is quite significant, although with some notes, including the position of OJK Regional 3 Central Java and DIY Yogyakarta which is only able to reach Islamic financial institutions (LKS) whose head office is located in Central Java and Yogyakarta, while LKS only has branch offices in Central Java and Yogyakarta Yogyakarta. Is the authority of the Regional OJK 3 of Central Java and DIYogyakarta, meaning that it is the domain of the authority of the Central OJK in Jakarta. The problem is if there is a violation or an act that is against the law, then the Regional OJK 3 of Central Java and D.I. Yogyakarta is only reporting or coordinating with the Central OJK. The Financial Services Authority (OJK) in Region 3 of Central Java and Yogyakarta Yogyakarta has carried out its function as an actress in the context of violations of law or criminal acts, in which the OJK has played a function as an investigator and then reported to law enforcement officials (APH ) and submitted to the judicial process. However, related to the implementation of the Microfinance Institution Law, OJK has not been able to carry out its function as a constitutional acter in enforcing Article 39 of the LKM Law regarding the existence of BMTs in the community which should abide and comply with licensing regulations under the OJKKeywords: Financial Services Authority, Muhtasib Institution, Sharia Financial Industry